THE IMPACT OF INDIVIDUAL LEARNER DIFFERENCES ON SECOND LANGUAGE ACQUISITION - Mavluda Yusupova (Galaxy International Interdisciplinary Research Journal, 2024)
The level of second language acquisition depends on many factors controlled by nature or shaped by nurture. The present paper studies the role of individual learner differences in second language acquisition (SLA). The individual differences, age, aptitude, motivation, cognitive style, learning strategies, and personality are defined and classified. A detailed review of the studies conducted in relation to the seven individual differences follows. The paper concludes by emphasizing that a language teacher must recognize the individual differences in his/ her students in order to impart effective language learning.